THE ANALYSIS OF OIL CONTENTS IN BANTAN BEACH BENGKALIS REGENCY RIAU PROVINCE - Antonius '; Yusni Ikhwan Siregar; Thamrin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study has been done in Bantan Beach of Bengkalis Regency in Riauin December 2014. This research aims to understand the analyze oil contentdistribution, observing the environmental conditions. The research used surveymethod. The samples were taken from three stations, The water qualityparameters measured were covering temperature, transparency, pH, salinity, andcurrent speed. The result showed the highest oil concentration highest tide was atthe station II,i.e: 0.189 ppm and lowest at stationIII,i.e:0.130 ppm. The highest oilcontent at low tide was at station III,i.e: 0.111ppm and the lowest was at station I,i.e 0.058 ppm. The water quality parameter at the highest tide was temperature31oC–32 oC; transparancy 46-48 cm; pH: 8; salinity: 30.3-31 ppt, currentspeed:0.17-0.24 and lowest tide were temperature of 30.3oC–31 oC; transparancy43-45 cm; pH: 8; salinity: 29.67-30 ppt, current speed:0.16-0.22 m/sec. Theresults obtained showed that the average oil content the tide was higher than theaverage oil content at low tide. The concentration of oil content in Bantan Beachshowed in the range support the aquatic organisms life.Keywords : The oil content, highest tide and lowest tide, Bantan Beach